The Squid and the Whale [videorecording (DVD)] - Daniels, Jeff, 1955-; Linney, Laura; Eisenberg, Jesse, 1983-; Kline, Owen; Baldwin, William, 1963-; Feiffer, Halley; Paquin, Anna (Sony Pictures Home Entertainment, 2006)
Based on the true childhood experiences of Noah Baumbach and his brother, the film tells the touching story of two young boys dealing with their parents' divorce in Brooklyn in the 1980s. The patriarch of an eccentric Brooklyn family claims to once have been a great novelist, but ultimately decided to settled into a teaching job. When his wife discovers a writing talent of her own, jealousy divides the family. The two teenage sons are forced to forge new relationships with their parents. Their mom begins dating her younger son's tennis coach. Meanwhile, dad has an affair with the student his older son is pursuing.